Penerapan Flipped Classroom Model Dalam Pembelajaran Identifikasi Risiko Pada Diklat Manajemen Risiko - Mustofa Kamal (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
This action research aims to assess the effectiveness of the Flipped Classroom model in risk identification learning. Risk identification subject is part of the Training of Risk Management. Models are chosen with consideration; the training participants are not familiar with risk identification and are always close to gadgets. The research method uses qualitative and quantitative. Learning effectiveness was assessed by trainer quantitatively, pre post test, and qualitatively, observations of two cycles of 64 participants from indonesian republic police, in 2 different timing class. Learning effectiveness was assessed also by participants through online surveys. The results showed that there was an increase in understanding of risk identification through an significant increasing in the average values in the both cycles. But, the increasing in second cycle, 1,20, are higher from first cycles, 0,70. While the results of the observation showed that the good activity of participants in study and discussion. In the other hand, a qualitative online assessment of 40,63% of participants shows 80,77% of participants asses the learning proses rated very well and 19,23% of participants rated it well. Keywords: flipped classroom model, risk identification.